Environmental law & policy in India : cases and materials - Divan, Shyam; Rosencranz, Armin (Oxford : Oxford University Press, 2022)
This publication scrutinizes almost every aspect of environmental law concerned with constitutional and legislative provisions, judicial remedies, and procedures.
This edition also issued in print: 2022.
Previous edition: 2001.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Environmental law -- India; Environmental policy -- India; Law; Laws of specific jurisdictions & specific areas of law